Association between impaired sensitivity to thyroid hormones and sedentary behavior: a cross-sectional study - Hangzhou Yang; Jie Kang; Lingkang Dong; Zihan Lin; Qixian Lin; Bo Wu (Frontiers in Medicine)
PurposeSedentary behavior and impaired thyroid hormone sensitivity are linked to a variety of comorbid conditions; however, the exact nature of their relationship remains inadequately studied. This study sought to examine the association between sedentary time and thyroid hormone sensitivity.MethodsUtilizing a cross-sectional design, the study analyzed data from U.S. participants in the National Health and Nutrition Examination Survey (NHANES) conducted between 2007 and 2012. The Least Absolute Shrinkage and Selection Operator (LASSO) regression and the Boruta algorithm were employed to screen out confounding factors closely associated with sedentary time and the parametric thyroid feedback quantile-based index (PTFQI). Multivariate linear regression models were applied to analyze the association between sedentary time and indicators of thyroid hormone sensitivity. After adjusting for all confounding factors, restricted cubic spline (RCS) curves were utilized to further explore the potential non-linear relationship between sedentary time and indicators of thyroid hormone sensitivity. Additionally, subgroup analyses and interaction tests were conducted to further explore this association.ResultsA total of 22 significant confounding factors were identified through LASSO regression and the Boruta algorithm. Among these potential confounding factors, body mass index (BMI) occupied a central position, and it partially mediated the association between sedentary time and the PTFQI. RCS analysis indicated that, after adjusting for all covariates, there was a significant linear association between sedentary time and PTFQI in men (P for overall = 0.002, P for non-linear = 0.085). In contrast, in women, the relationship presented an “inverted U-shaped” curve, which was not statistically significant (P for overall > 0.05). Moreover, the results of the interaction analysis revealed a significant interaction effect of race on the association between sedentary time and PTFQI (P for interaction = 0.004).ConclusionsIn this study, we found a positive association between impaired thyroid hormone sensitivity and sedentary time in men after adjusting for confounders, and BMI partially mediated this positive association. Additionally, the factor of race exhibited a significant interaction effect on the association between sedentary time and the PTFQI.